Causes for Conscientious Objection in Medical Aid in Dying: A Scoping Review - Triviño-Caballero, Rosana; Parra Jounou, Iris; Roldán Gómez, Isabel; López de la Vieja, Teresa (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2023)
In the light of current legislation on Medical Aid in Dying (MAiD; also known as euthanasia and assisted suicide) in different countries worldwide, there have been some arguments devoted to the right to conscientious objection for healthcare professionals in these specific practices. The goals of this scoping review are to provide an overview of the motivations and causes that lie behind conscientious objection identified by previous literature according to professionals’ experiences and to verify if these motives match with theoretical debates on conscientious objection. As the results show, there is a dissonance between the motivations included in the traditional and mainstream definition of conscientious objection used in theoretical and speculative frameworks and the actual factors that empirical studies note as reported motivations to object to MAiD. Hence, either we consider new factors to include as causes of “conscience”, or we accept that there are motivations that are not actually applicable to conscientious objection and should be addressed by other means. As conscientious objection to MAiD is multifaceted, there can be different kinds of motivations acting at the same time. It is thus pertinent to rebalance theoretical and empirical considerations to fully understand the complexity of the phenomenon and so provide insights on how to best deal with conscientious objection.